Safety and acute performance of paroxysmal and early persistent atrial fibrillation ablation using temperature-controlled, very high power, short duration catheter with a new radiofrequency generator. (19th May 2022) - Macle, L; Nair, GM; Skanes, A; Aguilar, M; Pantano, A; Khaykin, Y; Verma, A
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Biosense Webster Inc. Background/Introduction: The temperature-controlled contact force radiofrequency (RF) ablation catheter (QDM) has 6 thermocouples to maintain target catheter tip temperature and 3 tip microelectrodes for high local signal resolution. It has an enhanced irrigation profile to reduce char formation. Three prospective multicenter trials demonstrated safety and effectiveness of the QDM catheter using very high-power, short duration (vHPSD; 90W/4s), conventional power (CP; ≤50W) or combined modes. These studies were performed with an older RF generator. A new generator was developed to support the full suite of legacy, temperature controlled and multichannel ablation catheters, but has not yet been formally tested in a clinical setting. Purpose: Evaluate safety and acute performance of the QDM catheter with the new 90W-enabled generator. Methods: This prospective, multicenter study (4 Canadian sites) used vHPSD as primary mode for Pulmonary Vein (PV) isolation with overlapping 3mm lesion tags for anterior, inferior and roof of left atrium. Adjacent, non-overlapping lesions were used posteriorly to avoid esophageal heating. CP mode was used at operator discretion for thicker atrial tissue, touch ups, and non-PV triggers (Figure). Primary endpoint was confirmed entrance block in all PVs after adenosine and/or isoproterenol challenge. Acute procedural and safety data were assessed. Systematic char evaluation was performed. Results: Effectiveness analysis included 38/40 subjects with mean 110-day follow up (mean age, 61.7 ± 9.5 years; 63.2% male). Hypertension (47.4%) and congestive heart failure (15.8%) were the most common comorbidities. Fourteen subjects were treated with version V0 of the generator, and 24 subjects were treated using version V1c which included further software adjustments to the power titration, and current response to optimize performance. Combination vHPSD/CP workflow was used for PV isolation in 28 (75.7%) subjects and vHPSD was used solely in 10. A non-study catheter was used in 1 subject during connectivity troubleshooting. Primary endpoint of entrance block confirmation was achieved in 37/38 subjects and in all 37 subjects treated with study catheter only. No incidences of char or device-related adverse events were reported. There were no noted differences in the endpoints evaluated between the V0 and V1c groups. Median (Q1/Q3) RF application times for ablating PVs was 13.0 min (9.0/16.0) for the entire cohort. Median (Q1/Q3) time to achieve PV isolation in vHPSD-only group was 9 (7/12) min, and 14 (11/18) min, respectively. Conclusion(s): Consistent with data from prior 3 clinical studies, QDM catheter with the new 90W-enabled generator demonstrated the acute safety and effectiveness of temperature-controlled AF ablation with short PV ablation time and no char observed.